Titanium (IV) oxide anatase nanoparticles as vectors for diclofenac assessing the antioxidative responses to single and combined exposures in the aquatic macrophyte Egeria densa - Esterhuizen, Maranda (Ecotoxicology (London, England), 2023)
© 2023. The Author(s).